Nachweis von Flüssigkeit in den Nasennebenhöhlen als mögliches diagnostisches Zeichen des Ertrinkungstodes - Hottmar, P (Archiv fur Kriminologie, 1996)
A total of 387 cases of drowning in fresh water were investigated for the occurrence of liquid in sinus sphenoidalis and both left and right sinus maxillaris. About 75 per cent of the victims had positive findings of liquid in these cavities. This kind of investigation can be an auxiliary method in diagnosis of drowning.
Keywords: Diagnosis, Differential; Fresh Water; diferenciální diagnóza; lidé; sinus sphenoidalis; Female; mužské pohlaví; Drowning; utonutí; sinus maxillaris; Male; příčina smrti; sladká voda; Maxillary Sinus; Cause of Death; Sphenoid Sinus; ženské pohlaví; Humans